The ciliogenic transcription factor RFX3 regulates early midline distribution of guidepost neurons required for corpus callosum development. - Carine Benadiba; Dario Magnani; Mathieu Niquille; Laurette Morlé; Delphine Valloton; Homaira Nawabi; Aouatef Ait-Lounis; Belkacem Otsmane; Walter Reith; Thomas Theil; Jean-Pierre Hornung; Cécile Lebrand; et al. (PLoS Genetics)
The corpus callosum (CC) is the major commissure that bridges the cerebral hemispheres. Agenesis of the CC is associated with human ciliopathies, but the origin of this default is unclear. Regulatory Factor X3 (RFX3) is a transcription factor involved in the control of ciliogenesis, and Rfx3-deficient mice show several hallmarks of ciliopathies including left-right asymmetry defects and hydrocephalus. Here we show that Rfx3-deficient mice suffer from CC agenesis associated with a marked disorganisation of guidepost neurons required for axon pathfinding across the midline. Using transplantation assays, we demonstrate that abnormalities of the mutant midline region are primarily responsible for the CC malformation. Conditional genetic inactivation shows that RFX3 is not required in guidepost cells for proper CC formation, but is required before E12.5 for proper patterning of the cortical septal boundary and hence accurate distribution of guidepost neurons at later stages. We observe focused but consistent ectopic expression of Fibroblast growth factor 8 (Fgf8) at the rostro commissural plate associated with a reduced ratio of GLIoma-associated oncogene family zinc finger 3 (GLI3) repressor to activator forms. We demonstrate on brain explant cultures that ectopic FGF8 reproduces the guidepost neuronal defects observed in Rfx3 mutants. This study unravels a crucial role of RFX3 during early brain development by indirectly regulating GLI3 activity, which leads to FGF8 upregulation and ultimately to disturbed distribution of guidepost neurons required for CC morphogenesis. Hence, the RFX3 mutant mouse model brings novel understandings of the mechanisms that underlie CC agenesis in ciliopathies.